Graffiti Artist’s Historiographical Writing Model “Bansky” The Man Behind The Wall” in The Perspective of Johan Joachim Wincklemann - Suminto, RA Sekartaji; Carollina, Donna (Indonesian Journal of Visual Culture, Design, and Cinema, 2023)
History writing can be understood as a way of writing, exposing, or reporting the results of historical research that has been carried out as a matter of embodiment of research reports or historical writing itself. Furthermore, historical writing became known as historiography. Before writing the historiography of graffiti artists in Indonesia, it is necessary to understand the writing model that has been done by previous historians, one of which is Johan Joachim Wincklemann. Thisarticle will use a book entitled "Bansky: The Man Behind The Wall", to then review his historical writing style with Winckelmann's historiographical writing methodology. Although Jones in his book writes about Bansky's life, when viewed from the perspective of Winckelmann's historical methodology, there are still shortcomings in the process of writing Jones in this book. Thus from this review, it can be found that to create a good historiography for the writing of the history of graffiti artists requires closeness and accuracy in observing the work and graffiti artists observed.